RI 7360 Recovery Of Lead And Sulfur From Galena Concentrate, Using A Ferric Sulfate Leach - F. P. Haver (The National Institute for Occupational Safety and Health (NIOSH), 1970)
A procedure is described for recovering both lead and sulfur from galena flotation concentrate, comprising the following steps: (1) Aqueous oxidation of the concentrate, using ferric sulfate to convert lead sulfide to sulfate and to give elemental sulfur; (2) regeneration of the ferric sulfate by electrolysis in a diaphragm cell; (3) treatment of the leach residue with ammonium carbonate solution to change the lead to an acid-soluble form and to produce ammonium sulfate as a byproduct; (4) solution of the lead carbonate in hydro-fluosilicic acid followed by electrolysis to recover the lead as metal and regenerate the acid; and (5) extraction of the elemental sulfur from the final residue with an organic solvent. About 90 percent of the lead can be recovered by the above method as 99.9-percent-pure metal, together with two-thirds of the sulfur--half in the elemental form and half as ammonium sulfate.